Daytime sleepiness and academic performance among respiratory therapy students in Saudi Arabia: a cross-sectional survey - Mohammed M. Alyami; Ahmed H. Alasimi; Shahad Z. Albadani; Areen M. Alshehri; Rana A. Alqahtani; Abdullah A. Alqarni; Jaber S. Alqahtani; Abdallah Y. Naser; Hassan Alwafi; Saeed M. Alghamdi; Mansour S. Majrshi; Rayan A. Siraj; et al. (Discover Applied Sciences)
Abstract Background Excessive daytime sleepiness (EDS) is a prevalent concern among health-related students, but its incidence and impact on academic performance remain unexplored in undergraduate respiratory therapy (RT) students in Saudi Arabia. This study aims to determine the prevalence of EDS and its association with academic performance. Methods A cross-sectional online survey using the Epworth Sleepiness Scale (ESS) was distributed to RT students from January 5 to March 30, 2023. The prevalence of EDS was calculated using percentages and 95% confidence intervals, and logistic regressions identified associations with sociodemographic, sleep, and academic variables. Results Among 925 respondents, EDS prevalence was 32% (95% CI 23–35%). The overall mean ESS score was 8.31 ± 4.4, indicating a normal level of EDS. Current and ex-smokers were more likely to experience EDS than non-smokers [(OR): 3.28 (1.95–5.54), p < 0.001; (OR): 2.61 (1.35–5.07), p = 0.004]. Students with > 3 academic warnings had higher odds of EDS [(OR): 6.4 (1.98–20.71), p = 0.002]. Those napping ≥ 4 times weekly were 15 times more likely to experience EDS [(OR): 15.2 (6.94–33.35), p < 0.001], and students not sleeping before exams were 11 times more likely to report EDS [(OR): 11.3 (1.28–100.52), p = 0.029]. Conclusion EDS affects a significant proportion of RT students, with several sociodemographic, sleep, and academic factors contributing to susceptibility. Further research is needed to identify primary determinants and develop targeted interventions to mitigate EDS and its impact on academic performance.